Initial experience using a femtosecond laser cataract surgery system at a UK National Health Service cataract surgery day care centre. Issue 7 (27th July 2016) - Day, Alexander C; Dhallu, Sandeep K; Maurino, Vincenzo; Wilkins, Mark R
Abstract : Objectives: To describe the initial outcomes following installation of a cataract surgery laser system. Setting: National Health Service cataract surgery day care unit in North London, UK. Participants: 158 eyes of 150 patients undergoing laser-assisted cataract surgery. Interventions: Laser cataract surgery using the AMO Catalys femtosecond laser platform. Primary and secondary outcome measures: Primary outcome measure: intraoperative complications including anterior and posterior capsule tears. Secondary outcome measures: docking to the laser platform, successful treatment delivery, postoperative visual acuities. Results: Mean case age was 67.7±10.8 years (range 29–88 years). Docking was successful in 94% (148/158 cases), and in 4% (6/148 cases) of these, the laser delivery was aborted part way during delivery due to patient movement. A total of 32 surgeons, of grades from junior trainee to consultant, performed the surgeries. Median case number per surgeon was 3 (range from 1–20). The anterior capsulotomy was complete in 99.3% of cases, there were no anterior capsule tears (0%). There were 3 cases with posterior capsule rupture requiring anterior vitrectomy, and 1 with zonular dialysis requiring anterior vitrectomy (4/148 eyes, 2.7%). These 4 cases were performed by trainee surgeons, and were either their first laser cataract surgery (2 surgeons) or their first and second laser cataract surgeries (1 surgeon). Conclusions: Despite the learning curve, docking and laser delivery were successfully performed in almost all cases, and surgical complication rates and visual outcomes were similar to those expected based on national data. Complications were predominately confined to trainee surgeons, and with the exception of intraoperative pupil constriction appeared unrelated to the laser-performed steps.